Effects of Script Training to Improve Discourse in a Patient With Chronic Aphasia. - Hollo, Alexandra; Ensar, Büşra; Meigh, Kimberly M. (Perspectives of the ASHA Special Interest Groups, 2024)
Purpose: Script training is a well-known treatment designed to improve functional communication in patients with aphasia. In this clinical study, we examined the effects of low-tech script training for J.W., a 73-year-old patient with chronic nonfluent aphasia acquired at age 60 years. Method: Using a single-subject, multiple-baseline design across three scripts, we assessed the effects of script training on percent script correct (PSC) and words per minute (WPM). The study took place in a university-based outpatient clinic and consisted of six training sessions plus 15 min of recommended daily homework. We adapted standard procedures in accordance with J.W.'s individual strengths, limitations, and preferences. Results: J.W. reached criterion (PSC = 80%) within two to three training sessions across three scripts (pretreatment: M = 17%, posttreatment: M = 83%). Moreover, he improved in communication effectiveness, nearly doubling his rate of speech from pre- (M = 31.53 WPM) to posttreatment (M = 59.59 WPM) sessions. Conclusions: We conclude that a brief script training intervention improved the ability to communicate effectively and efficiently for this patient with chronic aphasia. Anecdotally, J.W. also reported using the scripts successfully outside of the therapy room on a regular basis and expressed an interest in using script training in the future. Although methodological limitations of this clinical study must be considered, low-tech script training appears to have benefited this patient's ability to engage in functional discourse even 13 years post-stroke.